Überzeugungen von Lehrpersonen zu digitalen Medien Eine qualitative Untersuchung zu Entstehung, Bedingungsfaktoren und typenspezifischen Entwicklungsverläufen - Knüsel Schäfer, Daniela (Studien zur Professionsforschung und Lehrerbildung, 2020)
Teachers' beliefs are considered to play a decisive role in the quality of their professional activities. When using digital media in schools and classrooms, specific beliefs about digital media are important in addition to general job-related beliefs. However, there are hardly any empirical findings on the development and change of such convictions. On the basis of professional biographical narrative interviews, the present study recorded the diverse convictions of teachers about digital media, reconstructed individual developmental trajectories and the associated conditions, and worked out different basic patterns on the basis of a typology.